LEVEL OF COMPLIANCE OF NARCOTICS VICTIMS IN TURNING MEDICAL AND SOCIAL REHABILITATION - Triadi, Rd (Journal of Islamicate Studies, 2019)
The condition of drug abuse in Indonesia is very worrying. According to the records of the National Narcotics Agency (BNN), Indonesian citizens who have been victims of abuse of illicit goods have reached more than 4 million. This paper will review the maslahah murshalah of Islamic law against narcotics, psychotropic substances and addictive substances (NAPZA), their abuse and prevention in the province of West Java. This research is an analytic descriptive type with a qualitative approach. The researcher took the setting in West Java. The research techniques using observation techniques, interviews and documentation as a data collection tool. Data analysis uses data reduction, data presentation and conclusion drawing. The findings of this study are that, the level of compliance of narcotics victims in undergoing medical and social rehabilitation, for children who use narcotics is still not in accordance with the existing legislation, namely where the existing regulations should be rehabilitated for children who abuse drugs, but this provision is not maximal applied, more children were convicted than rehabilitated.